2014
DOI: 10.5539/ibr.v7n6p186
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Wealth Maximization: Literacy and Planning Embedded Model

Abstract: The aim of this paper is to develop a conceptual framework for wealth maximization. The paper defines and presents conclusive issues pertaining to financial literacy, financial planning and wealth maximization and expect to paradigm a conceptual framework for a prospective investigation. The research attempts to ascertain the significance of demography, perception towards money and parental role on financial literacy, financial planning and wealth maximization. Further research is obligatory to validate empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…According to Sundarasen et al (2014), it has been universally renowned that money is a governing tool and a strong stimulus that shapes the behavior of making financial decisions. Isomidinova et al (2017) further stated that because of the growing importance of money in everyone's life, it is worth recognizing the perspective of people toward money.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Sundarasen et al (2014), it has been universally renowned that money is a governing tool and a strong stimulus that shapes the behavior of making financial decisions. Isomidinova et al (2017) further stated that because of the growing importance of money in everyone's life, it is worth recognizing the perspective of people toward money.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Attitude toward money is anticipated to serve as signs of healthy financial behavior (Shim et al, 2010). In exact, many studies have found that attitude toward money is significantly associated with the financial literacy of students (Albeerdy & Gharleghi, 2015; Isomidinova et al, 2017; Sorooshian & Seng Teck, 2014; Sundarasen et al, 2014; Thapa, 2015). Grounded by the above literature, it can be established that their perspective toward money has a strong impact on financial literacy.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Money-related education is imperative to guarantee the reasonable advancement of people and society. As per Bryant, financial development and supportability are established in people's money-related proficiency (Al-Matari et al, 2014;Sundarasen et al, 2014;Wise, 2013).…”
Section: Financial Literacy and Firm Sustainabilitymentioning
confidence: 99%